2015
DOI: 10.3390/pathogens4040793
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and Disease Tolerance to Staphylococcus aureus

Abstract: The Gram-positive bacterium Staphylococcus aureus is one of the most frequent pathogens that causes severe morbidity and mortality throughout the world. S. aureus can infect skin and soft tissues or become invasive leading to diseases such as pneumonia, endocarditis, sepsis or toxic shock syndrome. In contrast, S. aureus is also a common commensal microbe and is often part of the human nasal microbiome without causing any apparent disease. In this review, we explore the immunomodulation and disease tolerance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 140 publications
(206 reference statements)
1
20
1
Order By: Relevance
“…The America Disease Control Centers have reported that S. aureus is one of the most common causes of body‐related infections and distributes worldwide . Food poisoning caused by S. aureus enterotoxin accounts for 33% of total bacterial food poisoning in the USA.…”
Section: Bacterium Organismsmentioning
confidence: 99%
“…The America Disease Control Centers have reported that S. aureus is one of the most common causes of body‐related infections and distributes worldwide . Food poisoning caused by S. aureus enterotoxin accounts for 33% of total bacterial food poisoning in the USA.…”
Section: Bacterium Organismsmentioning
confidence: 99%
“…Staphylococcus aureus, a potentially lethal opportunistic pathogen, can cause local skin or soft tissue infections, as well as systemic infections, including bacteremia, pneumonia, osteomyelitis, endocarditis and toxic shock syndrome. This pathogen has been shown to modulate hosts’ immune responses via an IL‐10‐dependent mechanism, thus facilitating its persistence during infection . Leech et al .…”
Section: Breg In Bacterial Infectionsmentioning
confidence: 99%
“…Staphylococcus aureus is a Gram-positive bacterium that colonizes the skin and nostrils of most healthy individuals (Li et al, 2015; Mulcahy and McLoughlin, 2016). It is also a common cause of human diseases, ranging from minor cutaneous infections to invasive hematogenous infections, as observed in children and young adults with necrotizing staphylococcal pneumonitis (Gillet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%